Green preparation of iron-containing coatings with methionine hydroxyl analog chelated iron on Ti–6Al–4V alloy - Xueyu Wang; Xinying Lai; Dizhu Yue; Shufang Zhang; Rongfang Zhao; Rongfa Zhang (Journal of Materials Research and Technology)
It is important to fabricate Fe–containing coating on medical titanium alloys by using environmentally friendly solutions. In this study, methionine hydroxyl analog chelated iron (Fe–MHA), one kind of widely used feed supplement, was firstly selected as an iron–containing substance. Fe–containing coatings were successfully prepared on Ti–6A1–4V alloys by micro-arc oxidation (MAO) in a base solution of 10 g/L organic phytic acid and 5 g/L inorganic sodium phosphate added with 0, 1, 3 and 5 g/L Fe–MHA. The prepared anodic coatings with 1, 3 and 5 g/L Fe–MHA contained 3.09, 5.11 and 6.60 At.% Fe and were composed of Ti, TiO2 and Fe3O4. Fe–containing coatings achieve decreased surface roughness, improved coating hydrophilicity and increased bonding strength than that developed in the base solution. The study provides the environmentally friendly process to fabricate Fe–containing MAO coating on medical titanium alloys.